Education on Consuming Vegetables and Fruits as Sources of Antioxidants in Cancer Prevention among Students at SD Negeri 104242 Lubuk Pakam - Siti Aisyah; Winda Rizki Pebrina Batubara; Dian Novita; Edarni Zebua (JURNAL PENGMAS KESTRA (JPK), 2026)
Background: Cancer is a non-communicable disease whose incidence continues to rise and can be influenced by various factors, including lifestyle and dietary patterns from an early age. The habit of consuming low-fiber foods and minimal intake of vegetables and fruits in elementary school children has the potential to form unhealthy eating patterns that continue into adulthood. This condition can increase the risk of various degenerative diseases, including cancer. Vegetables and fruits are known to contain various important nutrients, especially antioxidants, which play a role in protecting body cells from damage caused by free radicals and supporting the body's defense system. Therefore, nutrition education from elementary school age is a strategic step in the prevention of non-communicable diseases. Objective: This Community Service (PkM) activity aims to increase elementary school students' knowledge and awareness of the importance of consuming vegetables and fruits as sources of antioxidants in the early prevention of cancer. Method: The activity was carried out at SD Negeri 104242 Lubuk Pakam through an interactive educational approach that included counseling, the use of visual media, educational games, and simple discussions tailored to the characteristics and level of understanding of elementary school children. Results and Discussion: The results of the activity showed an increase in students’ understanding from 60% before the education session to 85% after the session, representing a 25% increase in their knowledge of types of vegetables and fruits, the health benefits of antioxidants, and the importance of adopting healthy eating habits. Conclusion: This activity has the potential to be a preventive measure in shaping healthy lifestyles and increasing nutritional awareness from elementary school age.